The Application of Interactive Learning Media to Improve Grade 8B Malay Language Lessons at An-Nikmah Al Islamiyah Phnom Penh Instituute, Cambodia - Fika Amelia; Wandi Syahfutra; Deprizon; Neng Sholihat; Radhiyatul Fithri (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to improve students' Malay language learning outcomes at An Nikmah Al Islamiyah PhnomPenh Institute, Cambodia, through the application of interactive learning media. The method used is Classroom Action Research (PTK), which consists of four cycles: planning, implementation, observation, and reflection. The study was participated by 30 students who had difficulties in learning Malay Language. In each cycle, interactive media such as educational apps, learning videos, and language games were applied to increase student engagement and understanding of the material. Data collection was conducted through observation, interviews with students and teachers, and document analysis of learning outcomes. The results showed a significant increase in student engagement, where students' active participation increased from 31% in the first cycle to 51% in the second cycle and increased again to 83% in the third cycle. In addition, students' average test scores increased by 20% and 32% after the implementation of interactive media. The application of interesting and diverse learning media is proven to increase students' learning motivation and facilitate understanding of the material. The conclusion of this study confirms that the use of interactive learning media can effectively improve the quality of Malay language learning.